Geochemical effect of the rock chemistry and the anthropogenic activities on groundwater: The case study of NW Euboea, Greece - Kanellopoulos, C.; Mitropoulos, P. (Bulletin of the Geological Society of Greece, 2013)
A geochemical study of NW Euboea island ground waters was undertaken, in order to examine the possible effect of the chemical composition of the country rocks of the area as well as of the anthropogenic activities, to the concentration of environmentally important elements and chemical compounds in the groundwaters. NW Euboea consists of a great variety of rock types showing a wide range in mineralogical and chemical composition. The main groups of rocks occurring in NW Euboea are: i) various types of sedimentary rocks e.g. shale and chert formations, carbonate and clastic rocks, ii) ophiolitic rocks including peridotite, gabbro, serpentinite etc, and iii) epizonally metamorphosed basic igneous rocks, with schist and phyllite intercalations. A number of hot springs also occur in the area. The main anthropogenic activity in the area is the agricultural land use, as any significant industrial activity is absent. For that purpose, 45 water samples were collected and analyzed by Spectrophotometry for the main anions and by FP and AAS for major and a number of trace elements. On the basis of those analyses, a number of the water samples were selected and analyzed by ICP-AES and ICP-MS for a large group of mainly metallic trace elements. The interpretation of the analytical data showed clearly that the content of the groundwater for a significant group of trace elements (e.g. Cr, Ni, Zn) was considerably influenced by the chemical composition of the surrounding rocks, especially the ophiolitic and metamorphic rocks. The anthropogenic activities also affect the groundwater quality, near areas where the use of fertilizers and pesticides for agricultural purposes is extensive, resulting to the increase of various anion concentrations (NO3 -, SO4 -2, PO4 -3).